E-Assessment for Character Evaluation in Elementary Schools - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Fhadira Insani Putri; Rahmat Perdana; Rahmi Rahmi; Susbiyanto Susbiyanto; Febri Tia Aldila (Qubahan Academic Journal)
This study investigates Elementary School teachers’ responses to e-assessment tools for evaluating students' character traits of patriotism, tolerance, and discipline, and compares these traits across three schools. Utilizing a research and development methodology with quantitative data, the sample includes 55 students from Elementary School 034/I Teratai, 58 from Elementary School 045I Sridadi, and 61 from Elementary School 064/I Muara Bulian, selected through purposive sampling. Data were collected using a questionnaire and analyzed with descriptive statistics and one-way ANOVA, followed by Tukey HSD post-hoc tests. Findings reveal that Elementary School 034/I Teratai students scored highest in patriotism (89.11), Elementary School 045I Sridadi students in tolerance (88.41), and Elementary School 064/I Muara Bulian students in discipline (89.20). Significant differences in patriotism and discipline were observed between Elementary School 034/I Teratai and Elementary School 064/I Muara Bulian, and in tolerance between Elementary School 045I Sridadi and Elementary School 064/I Muara Bulian. The e-assessment tool developed was deemed highly valid and feasible for use. The impact of this e-assessment to make it easier for teachers to assess the character of high school students.